Husserl and the Philosophy as a Strict Science. Analysis from the Current Nihilistic Context (2011)
This work search for the purpose of Husserl in establishing a philosophy as a strict science in three topics: First, it points out some advances in the realization of such a goal ; secondly it establishes some reflections on the suggestion, referring to i